Perkembangan Motorik Kasar Anak Melalui Permainan Modifikasi Estafet Bola Di TK IT Daarush-Shohaabah Cikoneng - Raina, Ade; Sari, Amelia Cahya; Haerani, Salsya; Oktavianti, Riska Fitri; Hendasyah, Firza; Aura Maulida, Salma Azril; Oktavianingsih, Linda; Firmansyah, Andan (Yayasan Inspirasi El Burhani, 2024)
Introduction: One form of education is early childhood education, where the basics are physical growth and development (fine and gross motor coordination), intelligence, social emotionality, language and communication. Gross motor skills are one aspect of a child's development that must be optimized because they are very important for maximizing the growth and development of a child's body. To develop gross motor skills in children, this can be done by playing ball relay games. Objective: The aim is to determine children's gross motor skills through the modified relay ball game at Daarush-Shohaabah Cikoneng IT Kindergarten. Method: This community service was carried out at the Daarush-Shohaabah Cikoneng IT Kindergarten with a total of 48 children participating. This community service seeks to monitor gross motor skills in children by conducting observations and intervening or treating ball relay games to improve gross motor skills. Observation of gross motor skills is carried out by dividing them into several indicators, namely not yet developing, starting to develop, developing as expected and developing very well. Result: After the ball relay game treatment was carried out, the number of undeveloped indicators decreased to 2 children (4.17%), the indicators starting to develop became 4 (8.33%), the indicators developed according to expectations, 24 children (50%), In the very well developed indicator, there was an increase of 18 (37.5%). Conclusion : The conclusion is that the implementation of this community service activity went well according to what was desired and what had been planned. This community service has a positive value for the Daarush-Shohaabah Cikoneng IT Kindergarten students. This can be seen from the enthusiasm and activeness of the participants in carrying out the ball relay game activities and the results of the observations carried out which have good values ​​for the motor skills of children at the Daarush-Shohaabah Cikoneng IT Kindergarten.